2019
DOI: 10.1186/s12916-019-1390-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Caveat emptor’: the cautionary tale of endocarditis and the potential pitfalls of clinical coding data—an electronic health records study

Abstract: Background Diagnostic codes from electronic health records are widely used to assess patterns of disease. Infective endocarditis is an uncommon but serious infection, with objective diagnostic criteria. Electronic health records have been used to explore the impact of changing guidance on antibiotic prophylaxis for dental procedures on incidence, but limited data on the accuracy of the diagnostic codes exists. Endocarditis was used as a clinically relevant case study to investigate the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Hospitalizations of adult (�18 years old) patients diagnosed with IE were identified using ICD-10-CM codes and included in the study population, S1 Table in S1 File [16][17][18][19][20]. Patients discharged against medical advice (n = 768, 4%, unweighted) or with unknown disposition (n = 90, <1%, unweighted) were excluded since their course of care and clinical outcomes could not be reliably assessed.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Hospitalizations of adult (�18 years old) patients diagnosed with IE were identified using ICD-10-CM codes and included in the study population, S1 Table in S1 File [16][17][18][19][20]. Patients discharged against medical advice (n = 768, 4%, unweighted) or with unknown disposition (n = 90, <1%, unweighted) were excluded since their course of care and clinical outcomes could not be reliably assessed.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…The most recent comparable study using English data was published in 2015 [6] and reported an increase in the incidence rate of infective endocarditis following publication of the NICE guidelines. However, when we used different case definitions based on a recent study [17] and different statistical methods which identify the most likely date that trends changed, we found a wide range of likely dates for a change in incidence trends, leading us to conclude that there is no evidence for a direct link with the change in guidance in 2008. Although Criteria C implements the inclusion as reported in the earlier study [6], we found small differences in estimated incidence compared to this publication and found much higher and more stable coverage of secondary ICD-10 codes for organisms than previously reported, despite theoretically using the same underlying HES data.…”
Section: Discussionmentioning
confidence: 89%
“…Criteria A: At least one of the ICD-10 codes: I33.0, I33.9, I39.0, I39.8, I01.1, B37.6, or T82.6 in any diagnosis field, or I38 in the primary diagnosis field, in any episode in a superspell, where the patient was not discharged alive within 2 days, and excluding any readmissions within 30 days (using the HES patient ID as the patient identifier) Criteria B: ICD-10 code I33.0 in the primary diagnosis field, in any episode in a superspell, where the patient was not discharged alive within 2 days, excluding any readmissions within 30 days (using the HES patient ID as the patient identifier), and excluding elective admissions Criteria C: ICD-10 code I33.0 in the primary diagnosis field, in any episode in a superspell, excluding those with an admission method of "Elective -waiting list" Criteria A and B were shown by Fawcett et al [17] to represent the true number of infective endocarditis cases more accurately than simpler criteria, with Criteria A maximising sensitivity plus positive predictive value (PPV) and Criteria B maximising specificity plus PPV, while Criteria C was that employed by Dayer et al [6], the most prominent prior study based on national HES data.…”
Section: Incidence Of Infective Endocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al, use developed phenotypes to identify patterns of comorbidities in eMERGE network institutions [64]. That this work is far from easy is readily demonstrated by the difficulties described in other works, such as the study by Fawcett et al, in the UK [65] and that by Ando et al,in Japan [66]. Nevertheless, independent efforts to phenotype particular conditions still arise and show considerable promise.…”
Section: Phenotyping and Cohort Discoverymentioning
confidence: 99%